Herpetofauna, Espora Hydroelectric Power Plant, state of Goiás, Brazil. - Vaz-Silva, W.; Guedes, A. G.; Gontijo, F. F.; Barbosa, R. S.; Aloísio, G. R.; Oliveira, F. C. G. (Check List, 2007)
We provide a checklist of the herpetofaunal assemblage from Espora Hydroelectric Power Plant region(UHE Espora), southwestern of the state of Goiás, Brazil. Representatives of 32 amphibian and 71 reptile species wereobtained during faunal monitoring and faunal rescue programs carried out in the study area. The obtained species listand distribution records are here discussed in an attempt to improve the still limited knowledge on Cerradoherpetofaunal assemblages.